Identification of CDH4 Gene Copy Number Alteration and Its Association with Clinical Profile of Colorectal Cancer Patient - Ayu Dewi, Ni Nyoman; Rompis, Andreliano Yosua; Mulyawan, I Made; Ekawati, Ni Putu; Sun, H Sunny (http://dharmais.co.id/, 2024)
Background: The genes cadherin 4 (CDH4), Kirsten rat sarcoma viral oncogene homolog (KRAS), V-Raf murine sarcoma viral oncogene homolog B (BRAF), and microsatellite instability (MSI) each play a role in the development of colorectal cancer (CRC). CDH4 gene is located in chromosome 20q13.33 and its amplification or gain is the earliest mutational event found in the majority of CRC and colon polyps. This study aimed to identify copy number alteration in the CDH4 gene and its association with the clinical profile of CRC patients, including gender, age, tumor location and differentiation, frequency of BRAF and KRAS mutations, and MSI status. Methods: The DNA was extracted from 50 tumors and adjacent normal tissues based on the manufacturer’s instructions. Detection of MSI status was carried out by pentaplex polymerase chain reaction (PCR) and PCR products were size separated by capillary electrophoresis (CE) using an ABI 310 Genetic Analyzer. Both KRAS and BRAF mutations were identified by PCR and sequencing while CDH4 copy measurement was measured using TaqManTM Copy Number Assay. Results: Our findings showed 22 (44%) samples with no changes in the copy number of CDH4 gene. Interestingly, 21 (42%) cases had an amplification of the CDH4 gene or CDH4 gene gain, and seven (14%) cases decreased in CDH4 gene expression or CDH4 gene loss. We found an association between changes in the CDH4 gene and gender (p=0.001). However, there was no association between changes in the CDH4 gene and age (p=0.979), tumor location (p=0.145) and differentiation (p=0.648), the frequency of BRAF (p=0.171) and KRAS mutations (p=0.184) and MSI status (p=0.923). Conclusions: Copy number alteration in CDH4 gene in CRC patients and this alteration is significantly associated with gender. Further studies with a larger number of samples are essential to confirm this result and to identify the cause of CDH4 copy number alteration and its biological significance.